Effect Of Methodpicture Mapping On Ability Write Student Explanation Texts Class VIII SMPIT Gema Insan Cendikia - Wawan (Journal of Instructional Development, Innovation, and Evaluation, 2023)
The Influence of the Picture Mapping Method on the Ability to Write Explanatory Text of Class VIII Smpit Gema Insan Intellectual Students.The aim of this research is to determine the effect of methodPicture Mapping on students' ability to write explanatory text. In this research, the researcher used a quantitative research method. The researcher chose a research design which was carried out with a pre-experimental research design (one group pretest posttest design). The sample in this research was 30 students. This research proves that there is an influence of method usePicture Mapping on the ability to write explanatory texts. Keywords: Influence, Picture Mapping method, explanatory text